Peningkatan Literasi Masyarakat dalam Upaya Mitigasi Kekeringan di Dusun Tibu Lilin Kabupaten Lombok Barat - Saidah, Humairo; I Wayan Yasa; I Dewa Gede Jaya Negara; Hasyim; Rohani; I Dewa Made Alit Karyawan; Salehudin; Muh Bagus Budianto; Tri Rachmanto; Nur Chayati (Jurnal Pengabdian Magister Pendidikan IPA, 2025)
Drought is a major threat to the sustainability of water resources and environmental resilience in rural areas, such as Tibu Lilin in West Lombok Regency, where community understanding of mitigation strategies remains limited. This community extension program aims to improve local literacy and skills related to drought mitigation through the dissemination and demonstration of simple water conservation technologies. Methods used included group discussions, and demonstrations using images and videos of technologies such as rainwater harvesting systems, rorak trench, and introducing water-retaining plant species. Results demonstrated a high level of community participation, reflected in their enthusiasm and active participation during dissemination. In addition to enhancing community adaptive capacity to drought, this program directly supports the achievement of the Sustainable Development Goals (SDGs), specifically SDG 6 (Clean Water and Sanitation) by increasing knowledge about safe and sustainable water management, and SDG 13 (Climate Action) by strengthening community adaptive capacity to climate-related risks. Residents acknowledged that the knowledge gained was relevant to local conditions and useful for preparedness for recurring drought. Overall, the program successfully strengthened local capacity for drought mitigation and laid the foundation for the development of future initiatives focused on water resource conservation